Implementasi Kurikulum Merdeka dalam Mengatasi Krisis Belajar - Kunaenih, Kunaenih; Marlina, Yuli; Ulfah, Maria; Aminanti, Dian Safitri; Arsyad, Amirul; Sawkani, Ahmad (Universitas Indraprasta PGRI Jakarta, 2024)
This study aims to determine the implementation of the Merdeka Curriculum in overcoming the learning crisis at SD BPPI Cokroaminoto Pare. The method used is a qualitative method obtained from direct interviews to find out the planning and implementation of the Merdeka Curriculum carried out by teachers in overcoming the learning crisis at SD BPPI Cokroaminoto Kota Pare. In addition, observations and documentation were used regarding the implementation of the Merdeka Curriculum as part of understanding the basis of IKM. Based on the results of the interviews conducted, the Merdeka Curriculum has been implemented in addressing the learning crisis, but there is still a need for training, webinars, and peer sharing to better understand the Merdeka Curriculum. This is necessary for teachers to be able to understand in depth regarding the implementation of the Merdeka Curriculum. Teachers can provide interesting learning experiences for students so that the learning crisis can be resolved well and produce optimal learning.